Quantum confinement in semiconductor nanofilms: Optical spectra and multiple exciton generation - Khmelinskii, Igor (2017)
We report optical absorption and photoluminescence (PL) spectra of Si and SnO2 nanocrystalline films in the UV-vis-NIR range, featuring discrete bands resulting from transverse quantum confinement, observed in the optical spectra of nanofilms for the first time ever. The film thickness ranged from 3.9 to 12.2 nm, depending on the material. The results are interpreted within the particle-in-a-box model, with infinite walls. The calculated values of the effective electron mass are independent on the film thickness and equal to 0.17m(o) (Si) and 0.21m(o) (SnO2), with m(o) the mass of the free electron. The second calculated model parameter, the quantum number n of the HOMO (valence band), was also thickness-independent: 8.00 (Si) and 7.00 (SnO2). The transitions observed in absorption all start at the level n and correspond to Delta n =1, 2, 3,.... The photoluminescence bands exhibit large Stokes shifts, shifting to higher energies with increased excitation energy. In effect, nanolayers of Si, an indirect-gap semiconductor, behave as a direct-gap semiconductor, as regards the transverse-quantized level system. A prototype Si-SnO2 nanofilm photovoltaic cell demonstrated photoelectron quantum yields achieving 2.5, showing clear evidence of multiple exciton generation, for the first time ever in a working nanofilm device. (C) 2016 Elsevier B.V. All rights reserved.